Prarancangan Pabrik Asam Oksalat Dihydrate Dari Molasses Dan Asam Nitrat Kapasitas 17.000 Ton/Tahun - Ariska Putri, Fitriyani, Ir. Ahmad M.Fuadi, M.T., Ph.D (2017)
In the era of technological advances in various fields of rapid development, one of the future development prospects of building a factory that has competitiveness with overseas products. One of them is by building a plant oxalic acid. Oxalic acid is included in the simplest dicarboxylic acid (HOOC-COOH). The design of oxalic acid dihydrate plant with an area of 9600 m2 is planned to be built in 2020 and located in Gresik, East Java. The plant operates with a capacity of 17,000 tons / year, with consideration to meet domestic demand and reduce import dependence. The raw materials used in this design are molasses 727,08397 kg / hr and nitric acid (HNO3) 1606,13340 kg / hr with the help of catalyst (H2SO4) 460,11965 kg / h and (V2O5) 0.04601 kg / hr. This reaction takes place in the liquid-liquid phase, reversible, exothermic, and nonisothermal in a CSTR reactor with operating conditions of temperature 71oC and 1 atm pressure. To support the production process, it is necessary to establish a process support unit or utility which includes a water supply unit of 445,064,654 kg / hour, the required electricity of 1324,22655 kW, compressed air of 150 m3 / hour, and fuel requirement of 908,679 liters / Hr and laboratory. With the number of employees required 115 people where the work system consisting of employees shift and non-shift. From the economic analysis conducted on this factory with fixed capital Rp 95.761.307.111 and working capital of factory Rp 64.759.961.590 obtained Return of Investment (ROI) before tax is 32,5% and after tax is 24,4%. While Pay Out Time (POT) before and after taxes are 2.35 years and 2.91 years. Break Event Point and Shut Down Point by 42.45% and 22.96%. For Discounted Cash Flow (DCF) accounted for 37.64%. Based on the calculation of economic analysis it can be concluded that this factory worthy established. Keywords: Dihydrate Oxalic Acid, Oxidation Process of Nitrate Acid, CSTR